Chemokine subversion by human herpesviruses - Pontejo,S; Murphy,P; Pease,JE (Journal of Innate Immunity, 2018)
Viruses use diverse molecular mechanisms to exploit and evade the immune response. Herpesviruses, in particular, encode functional chemokine and chemokine receptor homologs pirated from the host, as well as secreted chemokine-binding proteins with unique structures. Multiple functions have been described for herpesvirus chemokine components, including attraction of target cells, blockade of leukocyte migration, and modulation of gene expression and cell entry by the virus. Here we review current concepts about how human herpesvirus chemokines, chemokine receptors, and chemokine-binding proteins may be used to shape a proviral state in the host.